A biomechanical approach to Cross-Training influences on running economy and performance - A comparative study between triathletes, long-distance runners and speedskaters - Hottenrott, K.; Hoos, O.; Sommer, H.-M. (1999)
NTRODUCTION: Cross-Training exercise is often used to increase running performance and reduce occuring loads on the musculoskeletal system. But it also has to be considered as a possible factor influencing optimized movement patterns and muscular performance of the primarily propulsive muscles in running (1). However, only few biomechanical data is available whether Cross-Training improves or diminishes running performance and economy (4). The aim of this study is to provide data on biomechanical parameters of ground contact during running by evaluating foot pressure distributions of specific trained athletes during a combined running and cycling test. METHODS: 12 athletes trained in running (6 longdistance runners (LDR), 6 triathletes (TRI)) of national level and 6 speedskaters (SKA) of the german national elite team) were tested after warm up and treadmill adaptation in a combined running and cycling test. All of them were rearfoot strikers. Test procedure: R1: Running step test (5-6 levels, each 3min, from 3,3m/s until full exertion) ; R2: Repetition of first level (3,3m/s) of R1 after 1min rest ; CST: Cycling step test (8-15 levels, each 3min, from 100 Watt to full exertion) after 3min rest ; R3: Repetition of first level of R1 (3,3m/s for 3 min) after 1min rest. Heart-rate and oxygen uptake were continually measured during the whole test procedure, lactate accumulation at each level, respectively. Foot pressure distribution (Novel, 100hz) and muscle activity (Biovision, 2000hz) of the primarily propulsive lower limb muscles were simultaneously recorded for 5 seconds at each level in running (R1, R2) and cycling (CST) and three times in R3 (R3a-R3c), respectively. Four consecutive steps were averaged and normalized in % of BW. RESULTS: Compared to R1 vertical displacement values decrease for both groups of LDR and TRI in R2 but increase in R3 above the base- value. Contrarily the values of the speedskaters remain stable in R2 and continuously increase from R3a to R3c. The reduction of vertical displacement values of LDR and TRI in R2 is mainly caused by a significant reduction in stance time (p<0,01). time-shifted towards toe-off. The obtained increases in vertical displacement values in R3 are all predominantly caused by a significant rise in average vertical force and thrust maximum (p<0,01). These results are in agreement with those of a similar previous study with triathletes (2). In comparison to findings of other studies on force platforms (3) the parameters stance time, thrust maximum and average vertical force are underestimated by approximately 10%. DISCUSSION: Our findings indicate that athletes trained in running (LDR and TRI), although their average force rises, possess the ability to reduce vertical displacement after intense running (top level in R1) while unaccustomed athletes (SKA) do not. An isometric-concentric cross-training exercise like cycling overrules this ability and causes diminished running economy and increased load on the musculoskeletal system. Considering the obtained EMG- and physiological parameters the optimization of stretch-shortening cycle performance and long term adaptations of muscle work in specific trained athletes have to be discussed as possible reasons for our results.